Finite element analysis on implant-supported bar with different geometric shapes - Peerakan Kupprano; Krid Kamonkhantikul; Woraporn Homsiang; Hidekazu Takahashi; Mansuang Arksornnukit (BMC Oral Health)
Abstract Background The selection guideline for the implant-supported bar connectors (ISBC) of hybrid denture is lacking. This study investigated the maximum von Mises stress (vMS), stress distribution, and displacement of various geometric ISBC in mandibular hybrid dentures, as well as the maximum principal stress (σmax) in the acrylic resin part, through finite element analysis. Methods Four different geometric cross-sectional patterns for mandibular ISBC—L, Y, I, and Square—of equal volume, based on the “All-on-4” concept, were created. Titanium alloy was used for ISBC with an acrylic resin wraparound. Models were integrated into the software and loading simulations mimicking mastication forces on posterior teeth in centric and eccentric loadings were performed. vMS was used for ISBC assessment, and σmax was assessed in acrylic resin. Results In centric loading, vMS was mainly at the distal screw channel across most ISBCs. Y ISBC showed the least vMS, while I and Square ISBC demonstrated uniform stress distribution on both sides; load and non-load-bearing sides. The others showed concentrated vMS only on the load-bearing side. Square ISBC exhibited the most displacement. In the acrylic resin region of each, σmax was found concentrated around the contact point between two adjacent denture teeth at different locations, with Square showing the highest σmax. Under eccentric loading, the maximum vMS of each model was found at the interface between the distal screw channel and the lingual aspect of the abutment, with comparable vMS. Square ISBC experienced the most significant displacement and showed the highest σmax within the acrylic resin juxtaposed with the screw channel. Conclusion The Y model of titanium-alloy in mandibular ISBC demonstrated the lowest vMS and displacement.